Bilateral Invasive Orbital Metastases from a Poorly Differentiated Large Cell Neuroendocrine Carcinoma of the Esophagus (2018)
We report a case of a 62-year-old man presenting with a right eye tumor and retinal detachment. A magnetic resonance imaging (MRI) of the skull showed hyperintense bilateral orbital masses exhibiting an intraocular component and an extraconal component in the right eye measuring 21.8 x 23.2 mm. Immunohistochemistry studies and histopathology results of our patient following right orbital exenteration confirmed a large cell neuroendocrine carcinoma. A positron emission tomography-computed tomography (PET/CT) scan was performed in an attempt to identify the primary origin detecting a metabolically active tumor located in the distal esophagus and metastases to the bone, liver, pancreas, left kidney, mesentery, abdominal, mediastinal and left axillary lymph nodes, choroid of the left eye and lumbar soft tissues. An upper endoscopy revealed an esophageal infiltrating mass. Immunohistochemical staining confirmed a poorly differentiated, large cell neuroendocrine carcinoma.